Corynebacterium matruchotii: A Confirmed Calcifying Bacterium With a Potentially Important Role in the Supragingival Plaque - Li, Qinyang; Zhou, Fangjie; Su, Zhifei; Li, Yuqing; Li, Jiyao (Frontiers in Microbiology, 2022)
Corynebacterium matruchotii is a reported calcifying bacterium that can usually be isolated from dental calculus and induce mineralization in vitro. In recent years, based on in situ hybridization probe and sequencing technology, researchers have discovered the central “pillar” role of C. matruchotii in supragingival plaque, and many studies focused on bacterial interactions in the biofilm structure dominated by C. matruchotii have been conducted. Besides, C. matruchotii seems to be an indicator of “caries-free” oral status according to imaging and sequencing studies. Therefore, in this review, we summarize C. matruchotii ‘s role in dental biofilm from the structure, interactions and potential connections with oral diseases.